Zagadnienie zwrotu społecznych nakładów na uzyskiwanie kwalifikowanej siły roboczej - Nowicki, Józef (Wydział Prawa i Administracji UAM, 1967)
Assuming that the cost of education of an engineer in 1963 in Poland amounted to about 670 000 zł in current prices, the question is being put forward how much time is needed for such a qualified worker to pay back to the community this sum of money. It seems to be reasonable to believe that rate of repayment is depending on the way an engineer is being employed. As there exists a lack of accurate figures on this matter, the author is trying to apply some sort of model analysis and is approaching the problem from both, productivity and salary points of view. At first he starts with the rate of growth of the national income that is assumed to be the result of a labour productivity of all the employed engineers only, but their productivity may result in the above mentioned rate of growth from 25% to 100%. Then the average salary in 1963 gives him an opportunity to suppose that the so called ,,value for the community" adequate to the Marxian surplus value) may swing from 25% to 150% respectively. In this way he is geting a relatively wide gap, which seems to include all the engineers no matter where and how they are employed. The above mentioned gap constitutes at the same time a proper answer to his basic question. As a result, the author comes to the conclusion, that approximately 5—15 years are needed for an engineer to repay to the community the education expenses (the so called unproduced value included) and 3,5—10 years — if the latter element is being excluded.
The repayment of expenditure for qualified workers